2008
DOI: 10.1093/nar/gkn441
|View full text |Cite
|
Sign up to set email alerts
|

Srs2 removes deadly recombination intermediates independently of its interaction with SUMO-modified PCNA

Abstract: Saccharomyces cerevisiae Srs2 helicase plays at least two distinct functions. One is to prevent recombinational repair through its recruitment by sumoylated Proliferating Cell Nuclear Antigen (PCNA), evidenced in postreplication-repair deficient cells, and a second one is to eliminate potentially lethal intermediates formed by recombination proteins. Both actions are believed to involve the capacity of Srs2 to displace Rad51 upon translocation on single-stranded DNA (ssDNA), though a role of its helicase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 35 publications
(70 reference statements)
8
42
1
Order By: Relevance
“…Indeed, deletion of ULS1 resulted in the accumulation of SUMOylated forms of Srs2 protein, while overproduction of Uls1 led to a decrease in the amount of Srs2-SUMO ( Figure 2B compare lane 2 with 4 and 6, and Figure S4B in File S1). The Srs2 SIM has earlier been demonstrated to be required not only for its binding to PCNA, but also for its SUMOylation under unperturbed conditions (Le Breton et al 2008;Armstrong et al 2012;Kolesar et al 2012). Consistently, we observed virtually no Srs2-SUMO conjugates in immunoprecipitates from transformants containing Srs2-R1 protein, devoid of SIM ( Figure 2B compare lane 2 with 8, 10, 12; and Figure S4B in File S1).…”
Section: Srs2 As a Target Of Uls1 Activitysupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, deletion of ULS1 resulted in the accumulation of SUMOylated forms of Srs2 protein, while overproduction of Uls1 led to a decrease in the amount of Srs2-SUMO ( Figure 2B compare lane 2 with 4 and 6, and Figure S4B in File S1). The Srs2 SIM has earlier been demonstrated to be required not only for its binding to PCNA, but also for its SUMOylation under unperturbed conditions (Le Breton et al 2008;Armstrong et al 2012;Kolesar et al 2012). Consistently, we observed virtually no Srs2-SUMO conjugates in immunoprecipitates from transformants containing Srs2-R1 protein, devoid of SIM ( Figure 2B compare lane 2 with 8, 10, 12; and Figure S4B in File S1).…”
Section: Srs2 As a Target Of Uls1 Activitysupporting
confidence: 88%
“…To investigate this possibility, we transformed wild type, uls1D, and a strain overexpressing ULS1 from a constitutive ADH1 promoter with plasmids harboring genes for SRS2 or srs2-R1, devoid of a SIM (Le Breton et al 2008;León Ortiz et al 2011), under the control of a copper-induced CUP1 promoter. We found that in the protein extract from the uls1D strain overexpressing the SRS2 gene, Srs2 protein migrated as a more profuse band of heavier molecular weight ( Figure 2A and Figure S4A in File S1).…”
Section: Srs2 As a Target Of Uls1 Activitymentioning
confidence: 99%
“…Accordingly, deletion of Srs2 SIM strongly reduces the interaction with SUMO and PCNA in the yeast two-hybrid assay (38,42) as well as the interaction with SUMO-PCNA in vivo and in vitro (38,(41)(42)(43). Srs2 recently was shown also to contain a PCNA-specific interaction site, which together with the SIM is necessary for efficient interaction with SUMO-PCNA (42,44,45).…”
Section: Homologous Recombination (Hr)mentioning
confidence: 99%
“…We previously showed that Srs2 sumoylation is dependent on the SIM of Srs2; therefore, its deletion should also abolish the interactions dependent on Srs2 modification (42). Because the Srs2 SIM motif is known to mediate its interaction with SUMO-PCNA (38,41,42,44), we also sought to differentiate between the PCNA-dependent and -independent roles of the SIM by using the Srs2 mutant lacking the PCNA interaction domain (Srs2⌬PIM). When testing the aforementioned Srs2 mutants for interactions with the known partners, we observed no significant effect in the case of Dun1, Lif1, Mph1, Pol32, and Slx5 (data not shown and Fig.…”
Section: Sumo Mildly Affects the Biochemical Activities Of Srs2mentioning
confidence: 99%
“…With the demonstration of the strippase activity, many of the phenotypes of srs2 mutants could be interpreted as a failure to prevent homologous recombination (HR), during both repair and rescue of stalled replication forks (Barbour and Xiao 2003;Watts 2006;Lambert et al 2010) and in other instances of mitotic HR (Robert et al 2006;Le Breton et al 2008;Burgess et al 2009;Kerrest et al 2009;Urulangodi et al 2015). The DNA helicase unwinding activity in vivo was demonstrated to be necessary to counteract the deleterious consequences of trinucleotide repeat sequences that could form stable hairpin structures during replication Lahue 2004, 2005;Kerrest et al 2009) and in unwinding at lesion sites produced by cleavage at rNMP residues in DNA to limit mutagenesis (Potenski et al 2014).…”
Section: Introductionmentioning
confidence: 99%